Functional Analysis of the Chemosensory Protein MsepCSP8 From the Oriental Armyworm Mythimna separata - Younas, Aneela; Waris, Muhammad I.; Tahir ul Qamar, Muhammad; Shaaban, Muhammad; Prager, Sean M.; Wang, Man-Qun (Frontiers in Physiology, 2018)
Chemosensory proteins (CSPs) play important roles in chemosensation in insects, but their exact physiological functions remain elusive. In order to investigate the functions of CSPs in the oriental armyworm Mythimna separata, in the present study we explored expression patterns and binding characteristics of the CSP, MsepCSP8. The distinctive functions of MsepCSP8 were also validated by RNAi. The results showed that MsepCSP8 shares high sequence similarity with CSPs of other insect family members, including the characteristic four-cysteine signature motif. MsepCSP8 mRNA was specifically expressed in antennae of females at levels well above those in other tissues. Competitive binding assays confirmed that 20 out of 56 ligands bound more strongly to MsepCSP8 at pH 7.4 than at pH 5.0. Protein structure modelling and molecular docking analyses identified amino acid residues involved in binding volatile compounds, and behavioural response experiments showed that M. separata elicited significant responses to five volatiles from compounds displaying high binding affinity to MsepCSP8. MsepCSP8 transcript abundance was decreased by dsMsepCSP8 injection, which affected the behavioural responses of M. separata to representative semiochemicals. Our findings demonstrate that MsepCSP8 likely contributes to mediating responses of M. separata adults to plant volatiles.